The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1088/1361-6641/ab2c0e
|View full text |Cite
|
Sign up to set email alerts
|

The conduction process of grain and grain boundary in the semiconductive zirconium oxynitride thin film

Abstract: Semiconductive zirconium oxynitride (ZrO x N y ) thin film was deposited on a sapphire substrate by reactive magnetron sputtering, and micro temperature sensors based on the film were fabricated by a microelectromechanical system (MEMS) micromachining process. The detailed structure of the ZrO x N y thin film was examined using x-ray diffractometer (XRD), scanning electron microscopy (SEM), field emission transmission electron microscope (FE-TEM), and the depth profiles of different elements and zirconium comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…reactive sputtering process. [25] Lin et al [26] found that the electrical conductivity of Zr x N y O z films is controlled first by thermal activation (300-75 K) and next by Mott variable range hopping (75-10 K).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…reactive sputtering process. [25] Lin et al [26] found that the electrical conductivity of Zr x N y O z films is controlled first by thermal activation (300-75 K) and next by Mott variable range hopping (75-10 K).…”
Section: Introductionmentioning
confidence: 99%
“…[ 24 ] Zr x N y O z has lately received attention due to its unique properties tuned by the admixture of nitrogen and oxygen during the reactive sputtering process. [ 25 ] Lin et al [ 26 ] found that the electrical conductivity of Zr x N y O z films is controlled first by thermal activation (300–75 K) and next by Mott variable range hopping (75–10 K).…”
Section: Introductionmentioning
confidence: 99%